The most commonly used methods of treatment for bruxism – a literature review - Wilmont, Paulina; Saczuk, Klara; Pawlak, Łukasz; Łukomska-Szymańska, Monika (Journal of Stomatology, 2018)
Bruxism is referred to as grinding and clenching of the teeth. It is a disorder affecting an increasing number of patients. This disease causes severe ailments that negatively influencing the daily functioning and manifesting, among the others, as toothaches, masticatory muscle pain, headaches, and tooth hypersensitivity. The aim of the work is to analyse the contemporary treatment methods and methods of alleviating the effects of the disease. In addition, it evaluates the usefulness of these methods in daily dental practice. The article shows the contemporary view of treatment, including the multidisciplinary approach. The authors present treatment methods of bruxism, such as: splints, physiotherapy, psychotherapy, biofeedback, and pharmacological treatment. The variety of methods currently used and the lack of clear guidelines for treatment of bruxism should be emphasised. The article also draws attention to the need to modify the daily behaviour of the patient through relaxation exercises or biofeedback, in order to eliminate bruxism and not just alleviate its symptoms. A multidirectional approach and treatment of bruxism can produce satisfactory and lasting results.